Effect of nickel nanofillers on the dielectric and magnetic properties of composites based on rubber in the X-band - Jamal, E. Muhammad Abdul; Mohanan, P.; Joy, Pattayil Alias; Kurian, Philip; Anantharaman, Maliemadom R. (Applied Physics A-Materials Science & Processing, 2009)
Nickel-rubber nanocomposites were synthesized by incorporating ferromagnetic nickel nanoparticles in a natural rubber as well as neoprene rubber matrix. Complex dielectric permittivity and magnetic permeability of these composites were evaluated in the X-band microwave frequencies at room temperature using cavity perturbation technique. The dielectric loss in natural rubber is smaller compared to neoprene rubber. A steady increase in the dielectric permittivity is observed with increase in the content of nickel in both the composites. The magnetic permeability exhibits a steady decrease with increase in frequency and magnetic loss shows a relaxation at 8 GHz. The suitability of these composites as microwave absorbers is modeled based on the reflection loss which is dependant on the real and imaginary components of the complex dielectric permittivity and magnetic permeability.

Flexible microwave absorber based on nickel ferrite nanocomposite - Sunny, Vijutha; Kurian, Philip; Mohanan, P.; Joy, Pattayil Alias; Anantharaman, Maliemadom R. (Journal of Alloys and Compounds, 2010)
Flexible magnetic composite materials were prepared by incorporating precharacterized nickel ferrite nanoparticles in a natural rubber matrix. The complex dielectric permittivity and magnetic permeability of the composites were measured at different microwave frequencies using the cavity perturbation technique. A steady increase in dielectric permittivity was observed with increase in filler concentration. Maxwell-Garnett mixture equations were employed to model the effective permittivity and permeability of the composite. Reflection loss was estimated by employing the model of single layer absorber backed with a perfect conductor. Reflection loss minima of -5.9 dB at 3.2 GHz for 12 mm thick rubber ferrite composite sheet is obtained in the S-band while a loss up to -16 dB could be achieved at 9.5 GHz in the X-band. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Cavity perturbation; Complex permeability; Complex permittivity; Microwave absorber; Nanocomposites; Nickel ferrite

Flexible microwave absorbers based on barium hexaferrite, carbon black, and nitrile rubber for 2-12 GHz applications - Vinayasree, S.; Soloman, M. A.; Sunny, Vijutha; Mohanan, P.; Kurian, Philip; Joy, Pattayil Alias; Anantharaman, Maliemadom R. (Journal of Applied Physics, 2014)
Flexile single layer electromagnetic wave absorbers were designed by incorporating appropriate amounts of carbon black in a nitrile butadiene rubber matrix along with an optimized amount of magnetic counterpart, namely, barium hexaferrite for applications in S, C, and X-bands. Effective dielectric permittivity and magnetic permeability were measured using cavity perturbation method in the frequency range of 2-12 GHz. The microwave absorbing characteristics of the composites were studied in the S, C, and X-bands employing a model in which an electromagnetic wave is incident normally on a metal terminated single layer. Reflection loss exceeding -20 dB is obtained for all the samples in a wide frequency range of 2-12 GHz when an appropriate absorber thickness between 5 and 9 mm is chosen. The impact of carbon black is clearly observed in the optimized composites on the mechanical strength, thickness, band width of absorption, dielectric properties, and absorptivity. (C) 2014 AIP Publishing LLC.

Stealth emulsion based on natural rubber latex, core-shell ferrofluid/carbon black in the S and X bands - Vinayasree, S.; Nair, Ajalesh Balachandran; Mani, Manoj; Archana, V. N.; Joseph, Rani; Mohanan, P.; Joy, P. A.; Anantharaman, M. R. (Nanotechnology, 2019)
A lossy dielectric with an appropriate magnetic property is one of the requirements of a stealth material. The thickness of the absorber and the corresponding bandwidth of absorption are also other deciding factors that determine the choice of the material as microwave absorbers. A stable emulsion, which is lossy as well as magnetic, is promising, since it can be coated on surfaces with required thickness in the desired band. A magnetic nanofluidic emulsion serves the purpose. A microwave absorbing emulsion based on natural rubber latex with core-shell magnetic nanoparticles, based on superparamagnetic iron oxide nanoparticles (SPIONs), was developed. The effect of additives like carbon black on the bandwidth of absorption was also studied as a function of weight percentage of carbon black. The complex dielectric permittivity and magnetic permeability were evaluated using a vector network analyser in the S and X bands. Furthermore, these results were modelled using surface impedance equations. These investigations revealed that the incorporation of carbon black enhances the bandwidth of absorption and an emulsion with the required dielectric permittivity and magnetic permeability can be tailored for stealth applications.
Keywords: carbon black; core-shell nanoparticles; ferrofluid; microwave absorbing paint; natural rubber latex